ABOUT PERSONAL EFFICIENCY OF MANAGERS IN HIGHER EDUCATION INSTITUTIONS: FIGHTING WITH TIME ABSORBERS - Marianna A. Lukashenko (Высшее образование в России)
Quality and efficiency of an institute of higher education activity depends not only on subdivisions that implement education process. Numerous subdivisions that are not directly engaged in providing education services must function with maximum effect. This dictates the necessity to pay attention to the personal efficiency of managers in highereducation and to consider the ways of optimizing their activity. The article examines severaltime management instruments that are directed at more rational organization of working time of an institute of higher education managers and employees, such as corporate agreements. Applying these instruments in the activities of institution of higher education forms corporate culture of time management and helps to optimize business processes.